“RUSSIAN PROPAGANDA” IN THE CONTEXT OF 2019 INDONESIAN PRESIDENTIAL ELECTION: POLITICIZATION OF NATIONALISTIC SENTIMENTS - Ahmad Nurcholis (Pusat Riset Politik BRIN, 2021)
This paper examines Russian allegations of propaganda that emerged throughout the campaign period during the 2019 simultaneous elections in Indonesia. The accusation was triggered by the heat of political tension during the election. The allegations of “Russian Propaganda” were first raised by the potential incumbent Jokowi in responding to many hoaxes and slander attacks produced by the opponents to strike him in influencing voter opinion. Jokowi's accusation made political tension even hotter. The opposing camp demands Jokowi to apologize to the Russian government for being considered to have made a statement not based on facts. Tension had increased when many media highlighted this issue and dragged Russian representatives in Jakarta. This article examines to what extent “Russian Propaganda” accusations emerged during the election affecting the two countries' relations. Keywords: Russian Propaganda, Indonesian Presidential Election, hoax, Jokowi